DEVELOPMENT OF LEARNING MEDIA USING ADOBE FLASH PLAYER SOFTWARE AND THE ROLE OF SELF EFFICACY TO INCREASE ECONOMIC LEARNING OUTCOMES FOR CLASS X IIS MAN 1 PADANG LAWAS - LAILA ROHIMA; Saidun Hutasuhut; Arwansyah Arwansyah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to create and develop learning media using Adobe Flash Flayer software in economics class X IIS MAN 1 Padang Lawas which can be used to support learning so as to assist teachers in delivering learning materials. This research is a development research with ADDIE development model. In addition, this study was also conducted to determine the interaction of Self Efficacy with the use of media in improving student learning outcomes. This research was conducted at MAN 1 Padang Lawas. The sampling technique was carried out by cluster random sampling technique. The results of this study are learning media with Adobe Flash Player Software developed that meet the eligibility requirements (valid) to be used as learning media in economics subjects for class X IIS. The product developed, based on an assessment of the media aspect, learning design and material aspects carried out by experts as well as responses or responses from students obtained an average percentage of 86.33% feasibility level so that the conclusion belongs to the "Very Eligible" category. There is an interaction between learning media and Self Efficacy on students' economic learning outcomes.